Structural Response of Post-Tensioned Slabs Reinforced with Forta-Ferro and Conventional Shear Reinforcement under Impact Load - Sandy Chaaban; Yehya Temsah; Ali Jahami; Mohamad Darwiche (Fibers)
Several researchers have studied how impact loads from impact hazards affect reinforced concrete (RC) slabs. There is relatively little research on impact loading effects on pre-stressed structures. The usage of fibers in structural elements intrigued researchers. In this paper, impact-loaded post-tensioned (PT) slabs with and without Forta-Ferro fibers were compared to post-tensioned slabs with plain concrete and conventional shear reinforcement. Forta-Ferro is a lightweight, low-cost fiber, and hence its effects on slab structural response under impact load deserve to be explored. Post-tensioned slabs’ impact resistance and energy absorption were tested using real-world situations of rapid and severe loads. Four identical 3.3 by 1.5 m concrete slabs were utilized in the experiment. The experiment involved dropping a 600 kg iron ball from 8 m onto each slab’s center of gravity. The slabs’ responses were investigated. The four slab configurations were tested for displacement, energy absorption, and cracking. Forta-Ferro fiber reinforcement is understudied, making this study significant. The study’s findings may help us comprehend fiber-reinforced concrete PT slabs’ impact resistance and structural performance. Engineers and designers of impact-prone buildings like slabs and bridges will benefit from the findings. The study also suggests adding Forta-Ferro fibers to post-tensioned slabs to improve durability and resilience against unanticipated impact hazards.